O financiamento da educação infantil no contexto do FUNDEB: limites e contradições na expansão do atendimento às crianças de 0 a 6 anos de idade em João Pessoa/PB – 2007 - 2013 - Santos, Joedson Brito dos (2015)
This research is about the childhood education financing in the context of the Fund for the Maintenance and Development of Basic Education and Educational Professional Valorization (Fundeb), and its central aim is to analyze in which ways the Fundeb is constituted as a capable policy to properly finance the expansion of the service for the childhood education as well as financing this segment in João Pessoa, Paraíba. The primary assumption is that the Fundeb is not able to finance adequately this segment for its institutional and financial framework is defined from the society structure and the economic, liberal and capitalist model which has in its scope, principles that limit the State action in providing its functions as well as defining the ways which must be taken for the advancement of the capitalist economy. The research discussed the historical, structural, contextual and situational aspects of educational financing policy in Brazil and the Financing of Early Childhood Education via Fundeb in order to understand their characteristics, advances, challenges and contradictions. There are discussions like the service expansion for children aging 0 to 6 in João Pessoa, Paraíba and the policy of public resource linking for this segment from 2007 to 2013. The investigation occurred through quantitative-qualitative approach and the case study was the methodological strategy. Furthermore, the historical retrospective was used as analysis technique and the documental analysis as research technique and instrument. The empirical research took place between 2007 – 2013, through data production and analysis in reports, documents and official databases (mainly online), available on the National Treasury site, in the Information System about Public Budget in Education (Siope) of the National Fund of Education Development(FNDE), at the National Institute of Pedagogical Studies and Research Anísio Teixeira (Inep), at the Brazilian Institute for Geography and Statistics (IBGE), at the Auditors Court of Paraíba, through the project Performance Indicators for the Public Expenditures in Basic Education in Paraíba (IDGPB), at the Municipal Secretariat of Education and Culture of João Pessoa, at the Municipal Education Plan (PME/2003/2015) and at the Education State Plan (PEE/2015). The data were produced and read based on the dialectical method which suggests starting from the given phenomenon to catch its movement, indicate its determinations and contradictions so that, afterwards, there can be the comprehension of the concrete reality. The historical importance of Fundeb and the Childhood Education Financing in this context can be realized. There are significant advances for the expansion and consolidation of the childhood education: offer enlargement, rising of service establishments, significant strengthening and increase of the resources for the segment provision. Nevertheless, there are also important links as the focus on elementary school, the resource insufficiency and the lack of criteria based on the studies on educational costs. The limits of this policy are placed on its own structure which has the liberal economic policy as its direction.